In-situ X-ray tomography analysis of the evolution of pores during deformation of a Cu-Sn alloy fabricated by selective laser melting - Samei, Javad; Amirmaleki, Maedeh; Ventura, Anthony P.; Pawlikowski, Gregory T.; Bayes, Martin; Misiolek, Wojciech Z.; Wilkinson, David S. (Additive manufacturing, 2020)
[Display omitted] In-situ uniaxial tensile tests coupled with X-ray computed tomography (XCT) were carried out on a Cu-4.3Sn alloy fabricated by selective laser melting. XCT models were constructed to enable step-by-step visualization of pore growth during deformation. Evolution of pores (mean diameter, density, volume fraction and sphericity) was quantified as a function of plastic strain. Evolution of the largest 7 pores existing in the as-printed part are individually characterized and coalescence is graphically presented. Results show that macroscopic instability begins once the largest internal pores reach the surface. Also, accelerated growth and coalescence of the largest 50 pores leads to rapid localization of strain followed by fracture. Pore growth was modeled using the Rice-Tracey (RT) and Huang models for different populations of pores and the parameters were optimized. The RT and Huang constants were found to depend on the initial mean pore diameter.